Digital Transformation in Banking: Assessing The Impact of Technological Innovation on the Performance of Public Sector Banks in South India - Hari , Dr. Sri; Kittur , Dr. Chaitanya; Policepatil , Dr. Siddanagouda; Rani , B.N. Sudha; Jwalapuram , Srihari; Rajshree, S.; Basha , S. Mahabub (International Journal of Accounting and Economics Studies, 2025)
The current research paper investigates the impact of embracing digital banking and advanced technologies on key banking outcomes, including operational efficiency, customer satisfaction, and bank profitability. Statistical analyses (including bar charts, correlation matrices, and regression models) were used to examine the relationships between these variables. It is evident from the results that digital banking adoption has the maximum mean score (4.4) signifying its prominent role in improving operational efficiency, customer satisfaction and profitability of banks. Table 3 shows a correlation study showing a high link between operational efficiency (0.72) and digital banking usage as well as bank profitability (0.75). These observations are further corroborated through regression analysis that confirms digital banking adoption as the strongest predictor of bank profitability (R² = 0.58). Lastly, AI and blockchain — advanced technologies also have a positive effect on all dependent variables by a slightly lesser degree than digital banking adoption. Digital banking Adoption Pie Chart Analysis – The data shows that the largest contributing factor (30%) to the the results of the study was related to Digital Banking adoption. Again, all these can be accessed through the research paper itself, which also highlights a few points that would serve the industry in moving forward.” In terms of how the findings would impact the industry, the study observes that the results show that more integration of digital banking services and modern digital technologies is needed to do well in banking performance and customer satisfaction. Based on these findings, the study suggests that banks focus on adoption of digital banking, deploy cutting-edge technologies, and constantly improve customer experiences. This study highlights the importance of banks in driving digital transformation and offers suggestions on how to stay competitive in an ever-evolving financial landscape.